The effects of exercise training and nutritional supplementation on taekwondo performance: a systematic review and meta-analysis - Xu, C.; Zhang, W.; Luo, L. (Frontiers in Nutrition, 2025)
Background: Taekwondo involves dynamic kicking and intermittent high-intensity efforts; the quantitative effects of training and supplementation on sport-specific outcomes remain unclear.